Studies on Mitotic Division of Allium ascalonicum L. Based on Observation Time - Annisa, Safitri; Widodo (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Cell is the little functional structure of living thing. It has important benefit of life. All of body activity is controlled by the genetic material in cell, as an example is cell reproduction. Cell Reproduction is an enhancing of cell generation by cell division (mitotic). Cell division of iving thing has different time each other. It depend to composition of material genetic comlpex and the environment factor such as nutrition, temperature and light intencity. So that it make difficult to learn about the process of mitotic division. Therefore this research has purpose to find the effective time of mitotic divison and learn about the mitotic division process. This research was conducted by using chromosomal preparation method and mitotic index calculation. The sample of this research is Allium ascaloniicum L. (shallot). Based on the research that has been done, Allium ascalonicum L. has highest mitotic index in afternoon at 12.00 WIB with percentage 31,6%. In evening at 15.00 WIB it has 28,3% and in morning at 09.00 WIB it has 18,4 %. The mitotic division consist of 5 phase, prophase, prometaphase, metaphase, anaphase, and telophase.